Distribution of dust color temperature, dust mass and planck’s function around C-rich AGB star: IRAS 19558+3333 using IRIS, AKARI, and WISE Surveys - Kandel, Ramchandra; Chaudhary, Ashok; Chaudhary, Keshab; Jalan, Muskan; Subedi, Anil; Khatiwada, Kushal; Upadhyay, Devendra Raj; Jha , Ajay Kumar (Scientific World, 2023)
The dust properties of C-rich AGB (Asymptotic giant branch) star IRAS 19558+3333 located at right ascension (R.A.) (J2000) = 19h 57m 48.440s and Declination (J2000) = +330 41h 21.250s was studied. The FITS image of this AGB star was obtained by SkyView Virtual Observatory in IRIS, AKARI, and WISE surveys respectively. The flux of ambient medium in the wavelength range of IRIS 60 μm and 100 μm, AKARI 90 μm and 140 μm and WISE 12 μm and 22 μm was calculated along with the physical properties like dust color temperature, dust mass, Planck’s function and visual extinction of the candidate at a distance of 3415.420 pc. The minimum and maximum dust mass is found to be 1.606× 1021 kg (8.030 × 10−10 M⊙), and 7.013 × 1020 kg (3.506× 10−10 M⊙) in IRIS, 2.739 × 1022 kg (1.369× 10−8 M⊙), and 1.292 × 1022 kg (6.460 × 10-9 M⊙) in AKARI and 2.297 × 1020 kg (1.148 × 10−10 M⊙) and 3.013 × 1019 kg (1.506 × 10−11 M⊙) in the WISE survey and the dust color temperature of the corresponding C-rich star average value was found to be 24.230 ± 0.229 K in IRIS, 16.780 ± 0.189 K in AKARI and 123.750 ± 0.430 K in WISE survey. The temperature in WISE was higher than that of the AKARI and WISE surveys.